Tärikh-i jughrāfiyā'ī Makkāh-i Mu'aẓẓamah, Madīnah-i Ṭayyibah : Ḥajj va 'umrah - ʻImādzādah, ʻImād al-Dīn Ḥusayn Iṣfahānī, 1908- (Maktab-i Qur'ān, 1970)
Geographical history of shrines in the holy cities of Mecca and Medina in Saudi Arabia and formalities of Hajj (pilgrimage); viewpoint of Shiite Muslims.